To die beautiful : a novel - Jackson, Buzzy (Dutton, an imprint of Penguin Random House LLC, 2023)
"Hannie Schaft, a young woman living in Nazi-occupied Holland, never intended to be a fighter. Her dream was to finish law school in Amsterdam and join the League of Nations. But when Hannie's two Jewish best friends are in danger, and she crosses paths with Resistance recruiters while doing volunteer work with refugees, she realizes she cannot deny the urgent cause at hand and the changes happening around her. Driven by outrage and a fierce protectiveness for her friends, Hannie quickly becomes a valued member of the Resistance movement. As the simmering menace of Nazi-occupied Holland reaches a boiling point, Hannie becomes ever more daring, assassinating powerful Nazis point blank, blowing up munitions factories, and constantly improvising with last-minute Resistance orders, even getting Hitler's notice who dubs her "the Girl with Red Hair." She also falls deeply in love with a dashing fellow resister at a tremendous cost and finds a chosen family with the other women in the resistance. And while humanity falls apart around her, Hannie's greatest weapon is her determination not to become a monster herself: blijf altijd menselijk. Stay human. A mantra that is sorely tested as the war nears its bitter end..."--